Cardiovascular disease risk communication in NHS Health Checks: a qualitative video- stimulated recall interview study with practitioners. Issue 5 (2021) - Gidlow, Christopher J; Ellis, Naomi J; Riley, Victoria; Cowap, Lisa; Crone, Diane; Cottrell, Elizabeth; Grogan, Sarah; Chambers, Ruth; Calvert, Sian; Clark-Carter, David
No abstract available